Prevalence of malocclusion among the age group of 15-25 years in Bangladeshi population - Jubayer, Shamim; Kader, Md Abdul; Sharmin, Salma; Sultana, Nasrin; Mamun, Mohammad Shamim Al (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Aims: A cross sectional study was carried out to explore the Prevalence of malocclusion among the age group of 15-25 years in Bangladeshi population. Material and methods: A total of 431 samples were purposively selected. Data were collected by oral examination, model and face to face interview using the structured questionnaire and a standard format was prepared to record the data. Results: The responded of the study were 17 to 25 years. Their mean ages were 20.64 ±1.61 years. Male 33% and female 67%. Among the respondent 82.6% have class I molar relation, 12.06% class II and 5.34 % class III molar relation. Among class I group 74% have malocclusion and 26% normal occlusion that is 78.42% respondent has malocclusion. In residential status 86% are urban. 96% of the respondent brushes their tooth two times and 4% once regularly. 13% of the respondent never visits dental chamber in their life time. Conclusion: Most common malocclusion was class I followed by class II and class III. The systemic implementation of preventive oral care and community oriented health programs are needed for the continuous promotion of oral health care of Bangladesh. Ban J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.8-11